'Sweetening' Pregnancy: Galectins at the Fetomaternal Interface. (14th February 2013) - Blidner, Ada G.; Rabinovich, Gabriel A.
<x xml:space="preserve">Abstract</x> Successful mammalian pregnancy relies upon acceptance of a semi‐allogeneic fetus by the maternal immune system. Lessons learned from studies on protective immunity to microbial infections and tumours, prevention of autoimmunity, and allograft rejection have contributed to delineate the mechanisms leading to T‐cell tolerance at the fetomaternal interface. Recent observations highlight the contribution of galectins, a family of endogenous glycan‐binding proteins, to critical biological events occurring during mammalian gestation, including immune cell tolerance, inflammation, implantation, and angiogenesis. These multifunctional lectins can hierarchically control a cascade of immunoregulatory events including the expansion, recruitment, and function of regulatory T cells, the promotion of tolerogenic dendritic cells, and the execution of T‐cell death programs. In addition, galectins can control cell adhesion and signaling events critical for implantation and are involved in fundamental processes linking tissue hypoxia to angiogenesis. In an attempt to integrate the regulatory roles of galectins to immunological and vascular programs operating during pregnancy. Here we outline the regulated expression and function of individual members of the galectin family within the fetoplacental unit and their biological implications for the development and preservation of successful pregnancies.